Vaccination in pregnancy: The role of the midwife - Caroline S. E. Homer; Caroline S. E. Homer; Nasrin Javid; Nasrin Javid; Kellie Wilton; Zoe Bradfield (Frontiers Media S.A., 2022)
Midwives are the front-line workers providing maternity care for women in many countries. The role of the midwife includes providing information about, and recommendations for, maternal vaccination in pregnancy and for the baby in the postnatal period. Vaccinations recommended in pregnancy include those to prevent influenza, pertussis, tetanus and now COVID-19. Vaccinations for the newborn baby include hepatitis B. Healthcare professionals play an important role in influencing decision-making around vaccination and midwives are key in supporting vaccination uptake. Midwives are strong influencer in women's decisions around vaccination for themselves and their babies. The COVID-19 vaccination programs have shone a light on vaccination in pregnancy especially as SARS-COV-2 infection has significant adverse effects in pregnancy. COVID-19 vaccination has been shown to be safe and effective in pregnancy. Despite this, there is vaccine hesitancy from pregnant women in many countries. Midwives play a unique role in the provision of care to women and families but they need specific support and information regarding vaccination in pregnancy. Targeted education, supportive mentoring and supervision and opportunities to lead innovative ways of ensuring vaccine access is logistically easy and possible are all needed. This Commentary outlines the key vaccinations recommended in pregnancy including COVID-19 vaccination and highlights some strategies to scale-up vaccination programs in pregnancy with a particular focus on the role of midwives.